Embodying punishment: emotions, identities, and lived experiences in women's prisons - Chamberlen, Anastasia (Clarendon studies in criminology, 2018)
A unique theoretical and empirical examination of women's embodied experience of imprisonment in England. The author examines how women's experience of prison can be understood through a sociological focus on the interaction between body and emotion.